MODEL PERMAINAN UNTUK PENGEMBANGAN SOSIAL EMOSIONAL ANAK TK KELOMPOK B - Suyatmin Suyatmin; Kurnia Dyah Anggorowati (STKIP Melawi, 2022)
Abstract: This investigation was proposed to books develop social emotional aspect of children in the Group B of Kindergarten by using the game model that were proper as an instructional media. The research and development sourced from Sugiono model which consists of several steps: (1) assessing the needs to identify the purposes; (2) conducting instructional analysis; (3) analyzing learners and material resources; (4) writing the objectives of the performance, (5) develop the instruments for the assessment; (6) developing instructional strategies; (7) developing and selecting the instructional materials; (8) design and do a formative evaluation for the study; and (9) revising the instruction; (10) mass production. The instruments that were used to gather the data were by interviewing, validated media exsperts, material experts, and questionaire to teachers. The specification product from this experimental results can be a book, as a reference for teaching material in order to develop the aspect of social emotional of children in the Group B of Kindergarten. Based on the experts evaluation and some practitioners, this book was appropriate with the curriculum and characteristic, and also effective and feasible to be applied as media for developing social emotional of children in the Group B of Kindergarten. Keywords: model, game, development, social emotional Abstrak: Penelitian ini bertujuan menghasilkan model permainan dalam bentuk buku untuk pengembangan sosial emosional anak TK kelompok B yang layak digunakan sebagai media pembelajaran anak TK. Penelitian dan pengembangan bersumber dari Sugiono, langkah-langkah penelitiannya: (1) menilai kebutuhan untuk mengidentifikasi tujuan; (2) melakukan analisis instruksional; (3) menganalisis peserta didik dan bahan materi; (4) menulis tujuan kinerja; (5) mengembangkan instrumen penilaian; (6) mengembangkan strategi instruksional; (7) mengembangkan dan memilih bahan instruksional; (8) merancang dan melakukan evaluasi formatif pembelajaran; dan (9) merevisi instruksi. (10) produksi masal. Instrumen yang digunakan untuk mengumpulkan data adalah wawancara, angket skala nilai validasi matari dan ahli media, serta angket bagi guru. Hasil penelitian ini berupa buku yang digunakan guru sebagai acuan untuk mengajar pengembangan sosial emosional pada anak TK. Berdasarkan penilaian ahli materi, media dan praktisi dapat disimpulkan bahwa model permainan untuk pengembangan sosial emosional sesuai dengan kurikulum, karakteristik, serta efektif dan layak digunakan sebagai media pembelajaran pengembangan sosial emosional pada anak TK kelompok B.Kata Kunci: model, permainan, pengembangan, sosial emosional